A curious case of splenic infarction (Indian Journal of Case Reports, 2018)
Splenic infarction is an unusual diagnosis in infectious diseases. It is relatively more common in typhoid fever as opposed to nontyphoidal salmonellosis (NTS). A young male presenting with fever, abdominal pain, and tender hepatosplenomegaly, was investigated. Radiological tests showed the presence of areas of splenic infarction and his blood culture revealed the growth of NTS species. Only 5% of NTS infection present with extraintestinal manifestation such as splenic infarction, while the majority of the cases manifest as gastroenteritis.